CHICKENPOX IN THE YAROSLAVL REGION. ECONOMIC EFFICIENCY OF VARICELLATION OF ONE AGE-GROUP OF CHILDREN - T. A. Druzhinina (Union of pediatricians of Russia, 2012)
Chickenpox is one of the mass infection diseases in Yaroslavl Oblast. In 2003-2011 chickenpox morbidity in Yaroslavl region was registered at the level of 362.02-870.00 per 100,000 people; in 2011 the number of patients reached 11,070 (10363 of them - children). The highest level of the chickenpox morbidity is registered among children. Annually chickenpox is rated the second by the number of patients in the structure of infectious morbidity and takes over 80% of the total of respiratory infections (without influenza and ARVI). In studying the specifics of chickenpox epidemiology in the region, rises of morbidity with a period of three years were found, but the rise in 2011 was much more intensive than the average figures for the long-term observations. At present, selective varicellation for the risk-group children is performed according to the regional immunization schedule, but this does not influence the level of morbidity and the number of the clinically severe cases of the disease having the features of meningoencephalitis. Pharmacoeconomic calculations' analysis shows that in the absence of a planned cohort varicellation the economic damage caused by the disease in Yaroslavl Oblast reaches no less than 110 million roubles per year. Varicellation economic efficiency evaluation in one age cohort of children has been performed and the conclusions about the expediency of planned vaccinal prevention against this infection have been made.